Sun protection knowledge, attitudes and practices: A Lebanese‐based survey - Divina Justina Hasbani; Nohra Ghaoui; Firas Haddad; William Abou Shahla; Serena Saade; Tarek Bandali; Zahraa Menhem; Dana Saade (Wiley, 2024)
Abstract Background Despite extensive research on sun protection, there remains a gap in certain populations like Lebanon. It is essential to assess how Lebanese adults handle sun exposure and its risks. Objectives To examine the knowledge and habits of sun protection use among adults in Lebanon and explore the possible association between a history of skin cancer or photo‐related disorder and sun protection behaviours. Methods We conducted a single‐centre cross‐sectional study on 1001 patients presenting to the American University of Beirut Medical Center dermatology clinics from August 2020 till April 2023. Participants were between 18 and 80 years of age and recruited by convenience sampling. Those younger than 18 years old or not proficient in English or Arabic were excluded. Results Among 1001 adults (mean age, 36.06 years [SD, 14.72]; 708 [71.08%] female), 512 (52.78%) use sunscreen, 449 (46.29%) do not and 9 (0.93%) do not know. Respondents with a history of a photo‐related condition (melasma, lentigos/freckles and rosacea) were significantly more likely to be sunscreen users (p < 0.001), but a history of skin cancer did not significantly increase the odds of using sunscreen (odds ratio, 1.42; 95% confidence interval, 0.79-2.56). Participants who reported obtaining their sun protection information from dermatologists and/or social media were associated with increased sunscreen use. Conclusions The results of this cross‐sectional survey suggest that half of the patients presenting to dermatology clinics at a tertiary care centre in Beirut tend to use sunscreen. Future investigations are needed to better understand the photoprotective awareness and practices of the Lebanese population. The lack of patients' behaviours towards skin protection should gear a nation‐wide campaign to improve these practices. Our outcomes indicate that dermatologists should be at the forefront of such campaigns tackling sun‐protective measures and skin cancer prevention, especially using social media platforms.